Resilience in Final Year Students Experiencing Quarter Life Crisis - Mellyana, Mellyana; Yendi, Frischa Meivilona (International Journal of Applied Counseling and Social Sciences, 2024)
Students who experience quarter life crisis have resilience skills. This study uses a quantitative method with a comparative descriptive research type. The number of research samples was 60 final year students selected using purposive sampling techniques . The instrument used was the Connor-Davidson Resilience Scale (CD-RISC) 25-item resilience questionnaire which has been adapted. The research findings show that: 1) The resilience of students experiencing quarter life crisis is generally in the high category . 2) There is no difference in the resilience of final year students experiencing quarter life crisis BK FIP UNP in terms of year of entry. To increase resilience in final year students who are experiencing a quarter life crisis , it is important to organize counseling services in universities to provide various counseling services that can help final year students understand their personal conditions, identify their problems and provide support tailored to the individual needs of students.